1997
DOI: 10.1029/96jd03678
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the quasi‐biennial oscillation and stratopause semiannual oscillation

Abstract: Abstract. Analysis of rawinsonde and rocketsonde data at Ascension Island (7.6øS, 14.4øW) and Kwajalein (8.7øN, 167øE) in 1962-1991 suggests that the quasi-biennial oscillation (QBO) in the middle stratosphere is synchronized with the seasonal cycle and that descending westerly phases of the stratopause semiannual oscillation (SAO) are strongly influenced by the underlying QBO. The effect of the seasonal cycle on the QBO in the middle stratosphere is revealed in two, perhaps unrelated, observations: first, a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 20 publications
6
54
2
Order By: Relevance
“…The QBO exerts filtering on the vertically propagating wave spectra, such that a QBO dependence of the SAO must be expected, and is indeed found (Burrage et al 1996). At the same time it is observed that the QBO westerly phases often start in SAO westerly phases (Dunkerton and Delisi 1997), so that the SAO and QBO are dynamically coupled to some degree. Also in CL90, the stratospheric SAO varies with the QBO, as seen in the deeper propagation of westerlies when the QBO westerly phase descends to the lower stratosphere, and the QBO westerly phases start from an SAO westerly phase (Fig.…”
Section: B the Semiannual Oscillationmentioning
confidence: 82%
See 1 more Smart Citation
“…The QBO exerts filtering on the vertically propagating wave spectra, such that a QBO dependence of the SAO must be expected, and is indeed found (Burrage et al 1996). At the same time it is observed that the QBO westerly phases often start in SAO westerly phases (Dunkerton and Delisi 1997), so that the SAO and QBO are dynamically coupled to some degree. Also in CL90, the stratospheric SAO varies with the QBO, as seen in the deeper propagation of westerlies when the QBO westerly phase descends to the lower stratosphere, and the QBO westerly phases start from an SAO westerly phase (Fig.…”
Section: B the Semiannual Oscillationmentioning
confidence: 82%
“…These waves are horizontally well resolved in most GCMs so that it was expected that middleatmosphere GCMs could simulate the QBO, provided that the vertical resolution is improved such that the vertical structures of these waves are well resolved. Only later it became clear that large-scale waves are not sufficient to explain the QBO (Takahashi and Boville 1992) and that gravity waves must play an important role (Dunkerton 1997). Currently, it is assumed that a broad spectrum must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the QBO and the SAO interact with each other. For example, the QBO and SAO periods are often synchronized (e.g., Dunkerton and Delisi, 1997;Krismer et al, 2013), and it has been suggested that the eastward phase of the SAO can initiate an eastward phase of the QBO (e.g., Kuai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely understood to arise from the interactions of upward propagating waves, initially excited in the troposphere and including both eastward and westward phase speeds (such as equatorially trapped Kelvin and Rossby-gravity waves, and a range of smaller-scale gravity waves). These waves respectively encounter critical layers where they break and dissipate, depositing zonal momentum into the mean flow in the stratosphere (Dunkerton and Delisi, 1997;Baldwin et al, 2001). Other examples in the stratosphere include at least two different types of semi-annual oscillation (SAO), which tend to be present at higher altitudes in the stratosphere Copyright c 2012 Royal Meteorological Society (Garcia et al, 1997), either close to the stratopause around 1 hPa or higher still in the mesosphere, and have a mean period of precisely 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…The QBO and the seasonal cycle and/or SAO have long been regarded as somewhat 'coupled' (Dunkerton and Delisi, 1997;Garcia et al, 1997;Baldwin et al, 2001), in such a way that the highly periodic rhythms of the seasonal cycle and SAO help to trigger, at least partially, the start of the downward phase of the QBO. Hampson and Haynes (2003) used a 3D mechanistic model to explore the possible phase alignment between the QBO and SAO, in which a partial locking was found between the QBO and certain phases of the annual cycle.…”
Section: Introductionmentioning
confidence: 99%